Perceptions of stakeholders about the role of health system in suicide prevention in Ghizer, Gilgit-Baltistan, Pakistan - Anila Anjum; Tazeen Saeed Ali; Nousheen Akber Pradhan; Murad Khan; Rozina Karmaliani (BMC, 2020)
Abstract Background Suicide is a serious global public health problem, with more than 800,000 people dying by suicide worldwide every year. 79% of suicides happen in Low and Middle-Income Countries (LMICs), where lack of national suicide prevention programs coupled with inadequate MH facilities for early identification and treatment of mental disorders add to seriousness of the problems. Although there is paucity of research, studies suggest that the rate of suicide in district Ghizer, Gilgit-Baltistan (GB), in northern Pakistan may be higher compared to rest of the country. Methods This study aimed to explore the perceptions of stakeholders about the role of the health system at District Ghizer, GB using a qualitative descriptive exploratory research design. A total of 12 face to face in-depth interviews were conducted from the stakeholders using purposive sampling technique. Results The study results led to three broad themes, 1) Suicide as A Social Issue, 2) Role of Health System in Suicide Prevention, and 3) Challenges for Health System in Suicide Prevention. Theme one was sub-categorized into; a) Perceived situations contributing to suicide, b) Environmental factors. Theme two was subdivided into; a) Major hurdles for Health system, b) Lack of MH services in the available health system. Theme three was subdivided into; a) Lack of collaboration across-sectors, b) Unavailability of MH professionals, and c) Financial issues. The study findings reveal that there are multiple challenges for health system including, lack of awareness on mental issues, shortage of resources and lack of collaboration in the community. Moreover, existing policies or strategies need to be modified to overcome the existing challenges for the effective prevention. Conclusion This study emphasized creating awareness about MH issues, introduction of school health programs, parental counseling session and strengthening of the health system by allocating suitable budget for MH issues and suicide prevention strategies.